Seven Years of Selective Genetic Screening Program and Follow-Up of Asymptomatic Carriers With Hereditary Transthyretin Amyloidosis in Bulgaria - Chamova, Teodora; Gospodinova, Mariana; Asenov, Ognian; Todorov, Tihomir; Pavlova, Zornitsa; Kirov, Andrey; Cherninkova, Sylvia; Kastreva, Kristina; Taneva, Ani; Blagoeva, Stanislava; Zhelyazkova, Sashka; Antimov, Plamen; et al. (Frontiers in Neurology, 2022)
Hereditary transthyretin amyloidosis (ATTRv amyloidosis) is a rare, autosomal dominant multisystem disorder resulting from extracellular deposition of amyloid fibrils formed by a destabilized mutant form of transthyretin (TTR), a transport protein produced predominantly by the liver. Aim: The aims of the current study are to demonstrate the Bulgarian experience with the programs for screening among high risk patient population during the last 7 years, to present the results from the therapy with TTR stabilizer in our cohort, as well as to stress on the importance of following up of asymptomatic carriers with TTR pathogenic variants by a multidisciplinary team of specialists. Material and methods: In 2014 a screening programme among high risk patient population for ATTRv was initiated in Bulgaria. On one hand it was conducted to identify new patients and families among people with “red flag” clinical features, while on the other hand, the program aimed to identify TTR mutation carriers amongst the families with already genetically proved diagnosis. Sanger sequencing methodology was used to make fast target testing of the suspected individuals for mutations in TTR gene. All of the identified carriers underwent subsequent evaluation for neurological, cardiac, gastroenterological and neuroophthalmological involvement. For those, who were considered as affected multidisciplinary treatment and follow up was provided. Results: As a result of a seven year selective screening program among high risk patient population and relatives of genetically verified affected individuals, 340 carriers of TTR mutations were identified in Bulgaria with the following gene defects: 78.53% with Glu89Gln, 10.29% with Val30Met, 8.24% with Ser77Phe, 2.06% with Gly47Glu and 0.59% with Ser52Pro. All of the affected displayed a mixed phenotype with variable age at onset and rate of progression, according to their mutation. From the 150 patients, treated with TTR stabilizer, 84 remained stable, while in another 66 patients the treatment was terminated, either because of polyneuropathy progression or due to death. A program for regular follow up of asymptomatic carriers in the last 3 years enabled us to detect the transition of 39/65 to symptomatic patients and to initiate treatment in a timely manner.